Intercell interference margin for CDMA uplink radio network planning - Dawy, Zaher (2004)
Cellular operators make use of radio network planning tools to determine the number of base stations required to cover an area of interest with a given traffic profile. These tools are based on a link budget analysis that takes into account the pathloss model in addition to various losses and power margins. The power margins compensate for sources of variation in the network in order to guarantee a bounded probability of outage and, thus, help in reducing the complexity of radio network planning tools. In CDMA cellular systems, the mean of the intercell interference is commonly used for coverage calculations and radio network planning. However, the intercell interference is a random variable that depends on the positions of the users in neighboring cells. In this work, we propose and calculate a new power margin that should be used in link budget analysis to compensate for variation in intercell interference. We show that not using the proposed margin leads to a notable increase in outage probability. The proposed margin is of particular interest to cellular operators and for the development of radio network planning tools.